1974
DOI: 10.1021/bi00719a001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the ribose binding protein as the receptor for ribose chemotaxis in Salmonella typhimurium

Abstract: The ribose binding protein of Salmonella typhimurium has been shown to be the receptor for ribose

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
59
1

Year Published

1976
1976
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 22 publications
5
59
1
Order By: Relevance
“…Yet this result is not simply explained because (as shown in Table 1) ribose cannot bind to the purified galactose receptor. Previous studies had shown a good correlation between the specificity of binding to the purified receptor and the specificity of response of the intact organism (14,16 (Fig. 4).…”
mentioning
confidence: 60%
See 3 more Smart Citations
“…Yet this result is not simply explained because (as shown in Table 1) ribose cannot bind to the purified galactose receptor. Previous studies had shown a good correlation between the specificity of binding to the purified receptor and the specificity of response of the intact organism (14,16 (Fig. 4).…”
mentioning
confidence: 60%
“…The purities of sugars were checked where necessary by chromatography on silica gel in isopropanol:ethyl acetate:water, 7:2:1 (vol/vol), visualizing with aniline phthalate, or on cellulose in n-butanol:ethanol:water, 25:16:9 (vol/vol), visualizing with alkaline silver nitrate. Strains ST1, ST48, and ST29 are derived from Salmonella typhimurium LT2 as described (14).The capillary assay was performed essentially as described by Adler (17) except that a capillary tube (Microcaps-Drummond Scientific) containing attractant was placed in the commercially supplied holder containing the bacterial suspension. Bacteria were grown to midlogarithmic phase at 300 and were centrifuged (5000 rpm, 15 min); the pellet was resuspended gently in Vogel-Bonner citrate buffer (18) at 8 X 108 cells per ml.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, amino acid taxis is much stronger (Mesibov et al, 1973); for instance, it is hard to see smooth swimming by B. subtilis following addition of sugar but easy following addition of amino acid. Secondly, amino acid chemoreceptors do not have a transport function (Ordal et al, 1978) but sugar receptors do (Adler & Epstein, 1974;Aksamit & Koshland, 1974;Hazelbauer, 1975;Hazelbauer & Adler, 1971 As a prelude to biochemical studies of the function of sugar chemoreceptors, we have sought to determine the sugar attractants and discover specificities of chemoreceptors for B. subtilis. Similar experiments have already been done for E. coli .…”
Section: Introductionmentioning
confidence: 99%